Developing an Android application in conjunction with BLE beacons 1 - Pek, Qiujun (Nanyang Technological University, 2022)
Bluetooth beacons are a class of Bluetooth low energy (LE) devices that broadcast their identifier to nearby portable electronic devices. The technology enables smartphones, tablets, and other devices to perform actions when near a beacon.